PERSEPSI MASYARAKAT TERHADAP KELESTARIAN HUTAN PAYAU DI DESA PODORUKUN KECAMATAN SEPONTI KABUPATEN KAYONG UTARA - Handayani, Erik; Muin, Sudirman; Fahrizal, . (Universitas Tanjungpura, 2018)
The majority of people at Podorukun village works as farmers and they have a vast rice field. The rice field is located near the mangrove forest which can potentially disrupt the preservation of mangrove forest it self. Besides, the peoples’s perception toward mangrove forest preservation essentially affect the existence of mangrove forest in podorukun village. The more positive the peoples’s perception, the more sustainable the mangrove forest. The study aims to describe the correlation between the people’s perception toward mangrove forest preservation and the level of income, knowledge, and dependency on the forest.This research was conducted through survey, which involved interview, the data were collected by applying purposive random sampling. The data was analyzed descriptively by using Chi Square statistic non-parametric and inferential using statistical test of Kendall Tau non-parametric Correlation. There were 84 heads of family as the respondents of this research. Result of this research showed that the perception trend is high, the income trend is low, the level of knowledge is high, the level of dependency on forest is high, and there is a non-significant positive correlation between the peoples’s perception and income, knowledge, and dependency level to forest.Keywords : forest preservation, Mangrove forest, the people’s perception